EFEKTIVITAS PERMAINAN TENIS MEJA DALAM METODE DIFERENSIASI UNTUK MENINGKATKAN KARAKTER SISWA KELAS IV DI SEKOLAH DASAR - Dalfah Nurwaliyah, - (2023)
Internalization of character-based education has an important role in the subject of Physical Education, Sports and Health (PJOK). The new independent curriculum is the trigger at this time with the demands that teachers must be able to facilitate students in the form of interests, talents and character. With the facts in the field, the character of students during learning is proven to be low. However, several factors cause low student character, one of which is teacher-centered learning methods. The purpose of this study was to determine the effectiveness of table tennis in the differentiation method to improve the character of fourth grade students. This study used the Classroom Action Research (PTK) method with the research design following the Action Research model. This research was conducted in four meetings with an achievement target of 85% consisting of three actions. First, the pre-action was realized through initial data with planning results 48%, implementation 49.2%, student activity 60% and learning outcomes 68%. Second, the implementation of actions that are realized through pre-action evaluation for d post action results is an increase in character activity (honesty, discipline, responsibility and selfconfidence) and learning outcomes. The three action posts that were realized as a result of pre-action processing and evaluation of the implementation of the action resulted in planning 87.41%, implementation 91.25%, student activity 89%, and learning outcomes 89%. So it can be concluded that the effectiveness of table tennis games in the differentiation method can influence student character and learning outcomes. Keywords: Character Education, Differentiation Method, Table Tennis Game